The amino acid sequence of beta-galactosidase of Escherichia coli. - Fowler, A V (1977)
The amino acid sequence of beta-galactosidase was determined. The protein contains 1021 amino acid residues in a single polypeptide chain. The subunit molecular weight calculated from the sequence is 116,248. The sequence determination, carried out mainly by conventional methods, was aided by complementation tests, by the use of termination mutant strains, and by a new immunochemical method. The five residue sequence Thr-Pro-His-Pro-Ala appears twice within the polypeptide chain, but no other striking homologous features are evident.